Pediatric Patient and Parental Anxiety and Impressions Related to Initial Gastrointestinal Endoscopy: A Japanese Multicenter Questionnaire Study - Shin-ichiro Hagiwara; Yoshiko Nakayama; Manabu Tagawa; Katsuhiro Arai; Takashi Ishige; Takatsugu Murakoshi; Hiroko Sekine; Daiki Abukawa; Hiroyuki Yamada; Mikihiro Inoue; Takeshi Saito; Takahiro Kudo; et al. (Scientifica)
Objective. To assess anxiety among pediatric patients and their parents related to initial gastrointestinal endoscopy. Methods. Patients aged <19 years undergoing initial gastrointestinal (GI) endoscopy and their parents were invited to complete a self-administered questionnaire related to endoscopy in 13 institutions in Japan. Results. The subjects were 128 children, aged 1 month to 17 years. Forty-eight patients (37.5%) underwent esophagogastroduodenoscopy (EGD), 32 (25%) underwent colonoscopy (CS), 39 (30.5%) underwent both EGD and CS, 3 (2.3%) underwent balloon enteroscopy (BE), 3 (2.3%) underwent capsule endoscopy (CE), and 3 (2.3%) underwent CE and other endoscopic procedures. In the preendoscopy questionnaire, the most common concerns of the patients and parents before undergoing the procedure were “Pain” (45% of the patients underwent EGD or BE via the oral approach, and 52% of the patients underwent CS or BE via the anal approach) and “Procedural accidents related to the endoscopy” (63% of parents). In the postendoscopy questionnaire, the most common difficulty that patients and parents actually experienced before and after undergoing the procedure was “Hunger.” Conclusion. A preparatory intervention including an explanation regarding specific concerns before initial GI endoscopy, which this study revealed, could reduce anxiety experienced by both pediatric patients and parents.